2014
DOI: 10.1097/der.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Shoe Allergic Contact Dermatitis

Abstract: Foot dermatitis is a widespread condition, affecting men and women of all ages. Because of the location, this condition may present as a debilitating problem to those who have it. Allergic contact dermatitis involving the feet is frequently due to shoes or socks. The allergens that cause shoe dermatitis can be found in any constituent of footwear, including rubber, adhesives, leather, dyes, metals, and medicaments. The goal of treatment is to identify and minimize contact with the offending allergen(s). The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 55 publications
7
42
0
Order By: Relevance
“…59 Ingredients from the mercapto mix might indeed be more common in shoes and boots (although closely followed by thiuram mix). 60,61 Colophonium and PTBFR are also common ingredients in shoes, which frequently cause ACD, and this is confirmed again in our data. 60 However, especially concerning gloves, the allergies that we found could be attributable to sensitization in the past.…”
Section: Specific Allergenssupporting
confidence: 88%
See 1 more Smart Citation
“…59 Ingredients from the mercapto mix might indeed be more common in shoes and boots (although closely followed by thiuram mix). 60,61 Colophonium and PTBFR are also common ingredients in shoes, which frequently cause ACD, and this is confirmed again in our data. 60 However, especially concerning gloves, the allergies that we found could be attributable to sensitization in the past.…”
Section: Specific Allergenssupporting
confidence: 88%
“…60,61 Colophonium and PTBFR are also common ingredients in shoes, which frequently cause ACD, and this is confirmed again in our data. 60 However, especially concerning gloves, the allergies that we found could be attributable to sensitization in the past. Bergendorff et al showed that there were no thiurams present in protective gloves used in healthcare in southern Sweden.…”
Section: Specific Allergenssupporting
confidence: 88%
“…The majority of our patients with foot dermatitis were diagnosed with ACD, highlighting the importance of patch testing any child with foot dermatitis when an allergic cause is suspected . Signs suggestive of ACD include but are not limited to symmetric involvement of both feet, involvement of maximum footwear contact locations, and chronic dermatitis with acute flares of vesiculation . Signs suggestive of a non‐ACD cause are involvement of the plantar flexure creases and the lateral aspect of the feet.…”
Section: Discussionmentioning
confidence: 97%
“…Allergic contact dermatitis affecting the feet is frequently due to shoes or socks, and the most common allergens reported to cause shoe dermatitis are chromate (in leather), rubber chemicals, adhesives and textile dyes . Allergic contact dermatitis with onset on the hands may occasionally spread to the feet and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…6 Allergic contact dermatitis affecting the feet is frequently due to shoes or socks, and the most common allergens reported to cause shoe dermatitis are chromate (in leather), rubber chemicals, adhesives and textile dyes. 7,8 Allergic contact dermatitis with onset on the hands may occasionally spread to the feet and vice versa. Sometimes, hands and feet are exposed to the same allergens causing allergic contact dermatitis on both sites, for example due to leather shoes and leather gloves, or rubber chemicals in shoes and gloves.. For irritant contact dermatitis and endogenous eczema, the concomitant presence of foot and hand eczema is less well explained.…”
Section: Introductionmentioning
confidence: 99%